Survei Tingkat Daya Tahan Kardiovaskuler Siswa-Siswi SMA Negeri 16 Bengkulu Utara: Survei Tingkat Daya Tahan Kardiovaskuler Siswa-Siswi SMA Negeri 16 Bengkulu Utara - Frengki Fransisco; Bojan Bjelica; Defliyanto Defliyanto (UNIB Press, 2023)
The research aims to scientifically determine the effect of hadang game training on dribbling agility. This type of research is experimental design and the research design used is one group pretest-posttest design. This research was carried out in the fields of SDN 81 Rejang Lebong in 2022. The population in this study were futsal extracurricular students at SDN 81 Rejang Lebong. The samples taken in this research were 30 students. The research uses an experimental method where the statistical analysis used in this research is the t test. As for the calculation results between the initial test and the final test, there is a significant influence. The calculation results state that the value of tcount = 23.697 > ttable = 1.699 with a level of α = 0.05, so Ho is rejected and Ha is accepted.Based on the results of research conducted, the hadang game has an influence on ball dribbling agility in extracurricular futsal at SDN 81 Rejang Lebong. Futsal extracurricular students' dribbling agility increased after receiving treatment in the form of a game of hadang.